The burden of multiple sclerosis variants in continental Italians and Sardinians. (October 2015) - Barizzone, Nadia; Zara, Ilenia; Sorosina, Melissa; Lupoli, Sara; Porcu, Eleonora; Pitzalis, Maristella; Zoledziewska, Magdalena; Esposito, Federica; Leone, Maurizio; Mulas, Antonella; Cocco, Eleonora; Ferrigno, Paola; et al.
Background: Recent studies identified > 100 non-HLA (human leukocyte antigen) multiple sclerosis (MS) susceptibility variants in Northern European populations, but their role in Southern Europeans is largely unexplored. Objective: We aimed to investigate the cumulative impact of those variants in two Mediterranean populations: Continental Italians and Sardinians. Methods: We calculated four weighted Genetic Risk Scores (wGRS), using up to 102 non-HLA MS risk variants and 5 HLA MS susceptibility markers in 1691 patients and 2194 controls from continental Italy; and 2861 patients and 3034 controls from Sardinia. We then assessed the differences between populations using Nagelkerke's R 2 and the area under the Receiver Operating Characteristic (ROC) curves. Results: As expected, the genetic burden (mean wGRS value) was significantly higher in MS patients than in controls, in both populations. Of note, the burden was significantly higher in Sardinians. Conversely, the proportion of variability explained and the predictive power were significantly higher in continental Italians. Notably, within the Sardinian patients, we also observed a significantly higher burden of non-HLA variants in individuals who do not carry HLA risk alleles. Conclusions: The observed differences in MS genetic burden between the two Mediterranean populations highlight the need for more genetic studies in South Europeans, to further expand the knowledge of MS genetics.